Case study -- India responds to international food safety requirements: food safety in food security and food trade - Sareen, Shashi (International Food Policy Research Institute, 2003)
As awareness grows about food safety issues, the need for countries to provide greater assurance about the safety and quality of food also grows....This brief reviews (1) how India utilizes the international framework for food safety standards set forth by the Codex Alimentarius Commission (hereafter referred to as Codex), and (2) how India provides safety assurances for exports and promotes access to international markets for exporters.